Development of the project duration regression model of preparing women-boxers to competitions - Приходько, Сергей Борисович; Князь, Наталія Володимирівна (Eastern-European Journal of Enterprise Technologies, 2015)
The regression model of the duration of the projects of preparing women-boxers to competitions based on training duration was considered. The aim of the research is developing of non-linear project duration regression model of preparing women-boxers to competitions based on training duration using Johnson transformation. The empirical data of training duration and empirical data of duration of preparing to women boxers to competitions were analyzed using mathematical statistic methods. The regression model was developed based on Johnson transformation using regression analysis methods. Regression model development approach based on Johnson transformation vs. approach based on common logarithmic transformation was compared. Non-linear regression model of duration of projects of preparing women boxers to competitions based on Johnson transformation have better characteristics than the model based on common logarithmic transformation. Therefore, the application of regression model based on Johnson transformation for duration estimation of projects of preparing women-boxers to competitions was recommended. At the present stage the research is the actual because it will enhance the effectiveness of training women-boxers to competitions because it will improve sportsmanship of boxers and enable them to achieve better results in competitions.